Penggunaan Teknologi E-Commerce Dan Pelatihan Fotografi Untuk Meningkatkan Pemasaran Produk Kelompok Mama Romi - Tamtelahitu, Trientje Marlein; Sirait, Jimmy Purwata Mangasi; Tomasila, Golda (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
The narrow marketing reach of organic vegetable products produced by the Mama Romi group is a problem in itself for the Mama Romi group because the vegetables they obtain are traditionally traded to the surrounding community and local traders who come to the location. It is known that the Mama Romi group is still limited in terms of digital marketing knowledge and product photography training, and also limited knowledge and skills in the field of ICT, namely the use of web-based e-commerce applications and WhatsApp e-commerce as a direct communication medium with potential buyers. The method for implementing Community Service activities through the Community Partnership Program (PKM) is carried out in 4 stages, namely (1) Preparation Stage; (2) Implementation Stage; (3) Evaluation; (4) Sustainability Program. This PKM activity can help independent partners in the process of developing ICT-based product promotions to the wider community, thereby creating new benefits that have an impact on increasing income.Keywords: organic vegetables; web e-commerce; whatsapp e-commerce